Dendroekološka analiza rasti smreke (Picea abies (L.) Karst.) v okolici dveh termoelektrarn - Levanič, Tom (Zbornik gozdarstva in lesarstva, 2006)
The main objective of this study was to investigate tree-ring width before, during and after onset of significant SO2 air pollution around coal-fired power plants Šoštanj (TEŠ) and Trbovlje (TET). The surviving trees showed relative large growth oscillations and the most obvious effect of air pollution caused by coal-fired power plant on tree-ring width (TRW) can be observed in narrower TRW, which is, among other, connected with needle loss in Norway spruce. This is evident on plots closer to TET - reference plot has significantly higher radial increment as heavily and moderately affected plot. Plots around TEŠ show smaller, but still significant difference, between heavily and moderately affected plot and reference. It was also proven, on all affected plots, that the affected trees showed reduced response to favourable climatic conditions compared to healthy trees and more sensitive response to unfavourable climatic conditions. The study of pointer years showed that only some negative pointer years on plots very close to source of pollution could be directly connected to the beginning and gradual increase in power plant production. Coal-fired power plants have significant influence on tree growth. Site productivity is not fully used, trees are under constant stress, they react very sensitively to environmental stresses (such as drought) and recovery is slower compared to healthy trees. By installing filters on coal-fired power plant TEŠ, significant reduction of emissions occur, on the other hand TET approach to solving this problem was by building a 360 m high chimney which, however, did not reduce the emission but rather dispersed them over a larger area. TRW on affected plots around TEŠ gradually increased and is now more or less similar to TRW on a reference plot. TRW around TET show similar trend, although this is not due to significant increase in TRW on affected plot but more to the TRW decrease on a reference plot.
Keywords: dendroekologija; onesnaženost zraka; Picea abies; prirastek; propadanje gozdov; Slovenia; Slovenija; smreka; žveplov dioksid